161k views
2 votes
Please help
5(b + 2) = -b - 32

User Jack Chen
by
4.8k points

2 Answers

1 vote

Answer:

b = -7

Explanation:

5b + 10 = -b - 32

Remove the parentheses

5b + b = -32 - 10

Move the terms

5b + b = -32 - 10

Collect like terms

Calculate

6b = -42

ANSWER: b = -7

User Tayyaba
by
5.4k points
4 votes

Answer:

b = -7

Explanation:

Step 1: Distribute 5 to ( b+ 2):

5b + 10 = -b - 32

Step 2: Add b (or 1b) to both sides of the equation:

5b + 10 + (1)b = - b - 32 + (1)b

6b + 10 = -32

Step 3: Subtract 10 from both sides of the equation:

6b + 10 - 10 = -32 - 10

6b = -42

Step 4: Divide both sides of the equation by 6 to isolate b:


(6b)/(6) = (-42)/(6)

b = -7

User Zannix
by
5.2k points